The European legal framework on cybercrime: striving for an effective implementation - Calderoni, Francesco (Crime, law and social change, 2010)
This article analyzes the European legal framework on cybercrime. Initially, it argues the challenges of cybercrime to traditional criminal justice systems. Subsequently, it focuses on the criminal law framework on cybercrime with a mainly European perspective. The European legal framework provides a three-path solution: the reduction of frictions among national legislations, the introduction of new investigative powers and the facilitation of international cooperation. The article presents and discusses each solution. Further, it argues that the effective implementation of the main legal instruments does not seem to depend on the legal enforceability of these international measures. Contrarily, other, non legal, factors such as national security, politics, the economy and the public opinion appear to stimulate the spontaneous implementation of the European legal framework. In this context, the added value of the EU action is rather low, although the Treaty of Lisbon and the Stockholm Programme may improve this situation in the long term.